The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1159/000014267
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Motility in Preterm Infants Treated with Indomethacin

Abstract: Objective: To determine in preterm infants with a patent ductus arteriosus (PDA) the effect of indomethacin treatment on spontaneous motor activity. Study Design: Motor activity was assessed from repeated videotape recordings in 32 preterm infants (≤33 weeks gestation). Sixteen infants required indomethacin therapy for treatment of PDA, 16 were control infants, matched for gestational age. Indomethacin (0.2 mg/kg i.v. in 5 min) was given thrice, with an interval of 12 h. One-hour recordings were made immediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…So far, 11 studies on 358 infants assessed by 90 observers revealed an agreement between 89% and 93% [Prechtl, 1990;Geerdink and Hopkins, 1993;Albers and Jorch, 1994;Bos et al 1997bBos et al , 1998aBos et al , 2000Cioni et al, 1997aCioni et al, , 1997cEinspieler et al, 1997Einspieler et al, , 2002Guzzetta et al, 2003]. The average kappa [Cohen, 1960] in another four studies on 108 infants assessed by 11 observers was 0.88 [van Kranen-Mastenbroek et al, 1992;Bos et al, 1997aBos et al, , 1998bCioni et al, 2000].…”
Section: Interobserver Reliabilitymentioning
confidence: 96%
“…So far, 11 studies on 358 infants assessed by 90 observers revealed an agreement between 89% and 93% [Prechtl, 1990;Geerdink and Hopkins, 1993;Albers and Jorch, 1994;Bos et al 1997bBos et al , 1998aBos et al , 2000Cioni et al, 1997aCioni et al, , 1997cEinspieler et al, 1997Einspieler et al, , 2002Guzzetta et al, 2003]. The average kappa [Cohen, 1960] in another four studies on 108 infants assessed by 11 observers was 0.88 [van Kranen-Mastenbroek et al, 1992;Bos et al, 1997aBos et al, , 1998bCioni et al, 2000].…”
Section: Interobserver Reliabilitymentioning
confidence: 96%
“…The pattern of cramped synchronized GMs is the easiest to spot because all or most of the limbs contract and relax almost simultaneously with a monotonous sequence. The method has been widely accepted and recognized [29][30][31][32][33][34][35][36][37][38][39][40] as a simple, noninvasive, and powerful diagnostic and prognostic tool, and we think that assessment of spontaneous motility is a substantial part of the neurological examination. Medical staff involved in the neurological follow-up of high-risk newborn infants could benefit from the gestalt approach, which can be learned through specific training courses.…”
Section: Commentmentioning
confidence: 99%
“…Moreover, substantial indications suggest that spontaneous activity is a more sensitive indicator of brain dysfunction than reactivity to sensory stimuli in reflex testing. Various studies [29][30][31][32][33][34][35][36][37][38][39][40] have demonstrated that in newborn…”
mentioning
confidence: 99%
“…5,6 In addition, a reduction of the quantity and quality of the spontaneous motor repertoire is reported. 7 Recent studies indicate that cerebral, renal, and mesenteric blood flow is not impaired if INDO is administered as a continuous infusion, whereas ductal closure rates are reported to be similar. 8,9 Hence, we changed our protocol for ductal closure in December 2001 from bolus infusions to continuous INDO infusion.…”
mentioning
confidence: 99%